The Terrifying Mystery of the Cave - Georgina Voss; Betti Marenko (DIID, 2024)
The exploration of systems that Georgina Voss proposes engages with their affective dimensions and the complex interplay between visibility, power, and the unknown, reimagined as The Terrifying Mystery of the Cave. This metaphor shifts focus from the expectation of solutions to an acknowledgment of the profound complexity and enigmatic nature of systemic challenges. Drawing on perspectives from cybernetics to design theory, this analysis interrogates the mechanistic metaphors dominating system thinking, situating them within broader socio-political and historical contexts. A central focus lies in the tension between what is visible and what remains hidden — what occurs “backstage” — and the ways these obscured layers shape the visible outcomes of systems. Deterministic framings of systems as controllable entities are critiqued, emphasizing their human-made origins and deeply ingrained ideological structures. The unknown emerges as a generative space, where unknowing becomes a means to rethink complexity and disrupt reductive narratives.